"Deep" <firstname.lastname@example.org> wrote in message news:email@example.com... > > Consider (1) below under the given conditions: > > XY = AB (1) > > Conditions: X, Y, A, B are odd integers each > 1. > The symbol (m, n) = 1 means m, n are coprime odd integers each > 1. > Example m = 3, n = 35. > (X, Y) = 1, (A, B) = 1 > > Statement:: Given (1) one gets: > > X = A and Y = B (2) or > > X = a and Y = b (3) where AB = ab, (a, b) = 1 > > Any valid comment upon the correctness of the Statement will be > appreciated. > > Deep
XY = AB
X = A and Y = B (obvious, above condition does not apply) (2) or
X = a and Y = b (3) where AB = ab, (a, b) = 1
the (a, b) = 1 does not need to follow as it is correct without the condition.